Egypt : Social and Structural Review - World Bank (Washington, DC, 2013)
A social and structural review (SSR) identifies the strategic policy priorities that are likely to yield the highest returns in terms of poverty reduction and development. This SSR identifies those priorities by providing a systematic evaluation of economic policy and structure in order to identify a) the main constraints on poverty reduction and long run development in Egypt and b) the sources of vulnerability, particularly as Egypt considers further global integration through entering into foreign trade agreements. The five priorities for reform include: 1) In order to maintain Egypt's robust economic performance of the late 1990s, the Government will need to continue to maintain stability of the macroeconomic environment by strengthening economic management which may have been pushed off-course by exogenous shocks in the latter half of the 1990s. 2) Trade liberalization remains as an unfinished and critical area for further reform. By sharply reducing tariffs and other trade taxes, especially on manufactures, Egypt can achieve productivity gains and wage growth. 3) It is important to revisit government regulations that increase the cost of doing business in Egypt. 4) Expenditures of the bottom half of population appear to be fairly compressed. 5) The quality of life of population is in part determined by public services such as those that enhance health, education, sanitation, clean water, and air quality.